2004
DOI: 10.1677/erc.1.00783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen deprivation due to breast cancer treatment

Abstract: Breast cancer is one of the main life-threatening diseases that a woman may have to face during her lifetime. The increasing incidence of breast neoplasia reported over the last few decades has led to widespread screening of women resulting in early diagnosis. One common but challenging question for most doctors, after the surgical excision of the lesion, is determination of the ideal adjuvant therapy for their patients for the achievement of maximum life expectancy with the best quality of life.Since the begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 80 publications
(76 reference statements)
1
9
0
3
Order By: Relevance
“…Finally, our results are in line with previous studies that have documented a strong association between hormonal therapy use and the prevalence of hot flushes/night sweats, and vaginal dryness 3,6,7,12,14,23,34,35 . The specific influence of hormonal therapy, i.e.…”
Section: Comparison With Previous Researchsupporting
confidence: 92%
“…Finally, our results are in line with previous studies that have documented a strong association between hormonal therapy use and the prevalence of hot flushes/night sweats, and vaginal dryness 3,6,7,12,14,23,34,35 . The specific influence of hormonal therapy, i.e.…”
Section: Comparison With Previous Researchsupporting
confidence: 92%
“…W metaanalizie przeprowadzonej przez Early Breast Cancer Trialists' Collaborative Group [5] stwierdzono, że ablacja jajników jako samodzielna metoda leczenia uzupełniającego w sposób istotny poprawia przeżycie bezobjawowe i całkowite u kobiet przed 50. rokiem życia. Zmniejszenie pozareprodukcyjnego wpływu hormonów płciowych jest przyczyną wystąpienia objawów zespołu klimakteryjnego i zaburzeń w układzie moczowo--płciowym oraz osteoporozy i innych niekorzystnych przemian metabolicznych [7,8]. Zmiany w organizmie u kobiet leczonych lekami hamującymi działanie jajników w RP wydają się być podobne jak u kobiet po menopauzie [8].…”
Section: Discussionunclassified
“…Zmniejszenie pozareprodukcyjnego wpływu hormonów płciowych jest przyczyną wystąpienia objawów zespołu klimakteryjnego i zaburzeń w układzie moczowo--płciowym oraz osteoporozy i innych niekorzystnych przemian metabolicznych [7,8]. Zmiany w organizmie u kobiet leczonych lekami hamującymi działanie jajników w RP wydają się być podobne jak u kobiet po menopauzie [8]. Stosownie analogów LHRH, a co za tym idzie -niedobór estrogenów, powoduje szereg objawów niepożądanych, m.in.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Studies [6,7] on the adjuvant treatment of patients with oestrogen receptor expression have demonstrated that the combination of suppression or ablation of ovarian function in conjunction with tamoxifen is considered to be safe and as effective as chemotherapy. The use of GnRH analogues (LHRH), resulting in oestrogen deficiency, causes a number of adverse events [8] such as reduction in bone mineral density, adverse metabolic changes and disturbances in the sphere of mental functioning. Changes in body composition (BC) of women treated with blocking ovarian function appear to be similar to post-menopausal ones [9,10].…”
Section: Introductionmentioning
confidence: 99%